2009
DOI: 10.1038/jhh.2009.35
|View full text |Cite
|
Sign up to set email alerts
|

Urinary albumin excretion is associated with true resistant hypertension

Abstract: Resistant (or refractory) hypertension (RH) is a clinical diagnosis based on blood pressure (BP) office measurements. About one third of subjects with suspected RH have indeed pseudo-resistant hypertension and 24-h ambulatory-blood pressure-monitoring aids to precisely identify them. Our aim was to determine those clinical, laboratory or echocardiographic variables that may be associated with subjects with sustained hypertension (namely true RH). We carried out a cross-sectional analysis of 143 patients consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 39 publications
(64 reference statements)
2
31
0
Order By: Relevance
“…Therefore, a glycemia level even below the threshold for the diagnosis of diabetes mellitus, is undoubtedly an important risk factor for the development of hypertensive cardiopathy. Similarly to the present study, other authors found creatinine levels below the threshold for chronic renal disease in patients with HTN and damage to target organs [58,59].…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, a glycemia level even below the threshold for the diagnosis of diabetes mellitus, is undoubtedly an important risk factor for the development of hypertensive cardiopathy. Similarly to the present study, other authors found creatinine levels below the threshold for chronic renal disease in patients with HTN and damage to target organs [58,59].…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, in untreated patients, an older age and a female sex were also related to the presence of white-coat hypertension. 12 Previous reports of patients with RH classified after ABPM have also observed that true resistant hypertensives more frequently have diabetes mellitus and target organ damage, such as left ventricular hypertrophy and microalbuminuria, 4,5 and the incidence of cardiovascular events was higher during the follow-up of those considered true RH. 6,7 With respect to age, although some authors have reported an older age in white-coat RH, 4,17 others related old age with true resistance.…”
Section: Discussionmentioning
confidence: 94%
“…This is also in agreement with previous reports where white-coat hypertension was present in 20% to 40% of patients attended in referral units. 2,4,5,7 Differences in the prevalence of white-coat RH were mainly attributed to the selection of either daytime or 24-hour as the criteria used for definition, as well as the cutoff value (130/80 or 135/85 mm Hg) used. Among different values obtained during ABPM, nocturnal BP is clearly the best prognostic indicator of the cardiovascular outcome, 7,20 so we chose 24-hour BP as the diagnostic criteria of true RH, because it contains both activity and resting BPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,5 In a study of 286 patients classified as resistant hypertensives (elevated CBP on at least three antihypertensive drugs), ABP monitoring confirmed true resistance to treatment in 56%, whereas the remaining 44% had the white coat phenomenon. 19 In a more recent study by Oliveras et al 20 in 143 patients with clinic RH, ABP monitoring confirmed RH in 72%, whereas 28% had white coat hypertension. These data are in line with the present study findings showing that despite the careful assessment of CBP in two study visits and after one pre-study visit more than one-third of subjects with CRH (36%) had low ABP (Figure 3).…”
Section: Discussionmentioning
confidence: 94%